À propos des recherches sur les terres noires urbaines : dépasser le concept d’attente - Mélanie Fondrillon (Archéologie Médiévale)
Dark earth dating to the late Roman and early Medieval periods currently represents an important prospective in urban archaeology. The recurrent discovery of these complex stratifications in Roman towns has lead to interrogations about ancient uses of the urban space and the processes of formation that have led to the apparent homogeneity of these deposits. For the last fifteen years or so, the development of geoarchaeological studies, carried out alongside excavations and traditional finds studies, show that dark earth is functionally diversified and that it reveals progressive changes affecting the relationship between the town and its inhabitants. It is thus now necessary to move on from a purely descriptive approach, to develop programmes of interdisciplinary studies in order to characterize the function of dark earth, and to grasp its diversity.